PENGARUH DISIPLIN KERJA TERHADAP KUALITAS PELAYANAN SURAT PENGANTAR PEMBUATAN AKTA TANAH DI KANTOR DESA MARIO KECAMATAN KULO KABUPATEN SIDENRENG RAPPANG - Rasni; Lukman; Asad, Muh.Arisal (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to analyze the influence of work discipline on the quality of services for issuing cover letters for making land deeds at the Mario Village Office, Kulo District, Sidenreng Rappang Regency. Work discipline is considered a key factor that influences the efficiency and effectiveness of public services. The research method used is a quantitative method with descriptive statistical analysis to describe work discipline conditions and service quality based on data obtained from observation, interviews, documentation and questionnaires. The research results showed that the level of compliance with working hours, superiors' instructions and office regulations reached 66%, 65% and 62% respectively. Service quality is measured through several indicators such as direct evidence (72%), reliability (72%), responsiveness (73%), assurance (68%), and empathy (72%). Factors that influence work discipline include goals and abilities (78%), leadership example (49%), employee salaries (74%), justice (62%), supervision (62%), legal sanctions (58%), firmness (65%), and human relations (47%). In conclusion, although several aspects of work discipline and service quality are considered quite good, there are still several areas that require further improvement, such as leadership and relations between employees and the community By understanding the relationship between work discipline and service quality, appropriate corrective steps can be taken to improve service quality, improve the image of local government, and better meet the expectations and needs of the community. Training, coaching, enforcing rules, and regular evaluation of employee performance are several steps that can be taken to achieve this goal.